Factors that influence the use of Strategic Management Accounting (SMA) in Malaysian Government-Linked Companies (GLCs) / Mohamad Hafiz Rosli, Jamaliah Said and Farahwahida Mohd - Rosli, Mohamad Hafiz; Said, Jamaliah; Mohd, Farahwahida (Accounting Research Institute & Faculty of Accountancy, 2014)
This study examines the factors that influence the use of Strategic Management Accounting (SMA) techniques among Malaysian Government-Linked Companies (GLCs), business strategy, and information technology (IT). This study also examines how the relationship infl uences firm performance. GLCs have successfully played a signifi cant role in contributing to the Malaysian economy. GLC performance is reportedly going through a good phase, but some GLCs still underperform. Data were collected via questionnaires answered by 70 federal and state owned Malaysian GLCs. Results show that certain SMA techniques, such as attribute costing, are highly used in Malaysian GLCs. Life cycle costing is least used. The study also reveals that business strategy and IT have signifi cant relationships with SMA usage. SMA usage also had a signifi cant relationship with firm performance. The findings would provide further understanding on SMA technique usage, particularly the factors that influence usage and enhance firm performance.